PERLINDUNGAN HUKUM BAGI TENAGA KESEHATAN DALAM KASUS KEKERASAN DAN TUNTUTAN MALPARAKTIK DI INDONESIA - Dara, Difa Mutia; Rosmalinda (As-Siyadah, 2024)
Health workers in Indonesia have an essential role in providing medical services, but they face serious challenges due to increasing cases of violence and malpractice lawsuits. In 2022, there were 134 cases of physical violence against medical workers, with most incidents occurring in hospitals and community health centers. This violence has a negative impact not only on the individuals involved, but also on the overall quality of health services. In the legal context, various regulations, such as Law Number 36 of 2014 concerning Health Workers, provide legal protection to health workers. Article 57 guarantees the right of health workers to receive legal protection, while Article 66 protects them from malpractice lawsuits if the procedures carried out have met standards. However, the implementation of legal protection still faces various obstacles. This study uses a normative legal method with a descriptive-analytical approach, aiming to analyze existing legal protection and its challenges. Data were obtained through literature studies and qualitative analysis. The findings show that existing legal protection is not yet fully effective, with many health workers feeling vulnerable to violence and lawsuits. Stronger protection is needed to prevent violence and unwarranted lawsuits. In addition, the role of government, hospitals, and professional associations is very important in strengthening the legal protection system. The establishment of stricter regulations and the dissemination of information on the rights and obligations of health workers are expected to improve their safety in carrying out their duties. With these steps, it is hoped that health workers can work more calmly, which ultimately contributes to improving the quality of health services in Indonesia.